EL MUNDO FÍSICO DE ARISTÓTELES - JOSE DUARTE (Universidad Distrital Francisco José de Caldas, 2011)
Aristotle raised the most popular of the Greek theories about the universe and the bodies movement. In this paper I collect and integrate scattered ideas in the literature about the physical world of Aristotle, dividing this paper in two parts. The first talk in general about Aristotelian philosophy and his contributions to human knowledge. The second deals specifically Aristotelian mechanics and geocentric universe. This paper shows how Aristotle was more concerned with the movement causes than its description, relying primarily on philosophical methods.